The Influence of Substrate Width Ratio on the Rectified DC Output Voltage of a Piezoelectric Energy Harvester - Agung Dwi Santoso; Adhes Gamayel; Untung Suprihadi (Journal of Global Engineering Research and Science, 2025)
Piezoelectric energy harvesters (PEHs) have attracted considerable attention as an alternative approach for converting ambient mechanical energy into electrical power, particularly under low-speed wind conditions. In this study, the performance of a micro-windmill-driven piezoelectric wind energy harvesting system is experimentally investigated with emphasis on the effects of wind speed and mechanical configuration ratios. Experiments were conducted in a controlled wind tunnel environment at wind speeds of 6, 7, and 8 m/s to represent low to moderate airflow conditions commonly encountered in practical applications. Three mechanical configuration ratios, namely 1:3, 1:2, and 1:1, were evaluated to assess their influence on the dynamic response and electrical output of the piezoelectric element. The alternating voltage generated by the piezoelectric harvester was rectified, and the output voltage–time characteristics were recorded over a 60 s testing period using a data acquisition system. The experimental results demonstrate that increasing wind speed significantly improves both the voltage rise rate and the achievable steady-state voltage for all tested configurations, indicating enhanced mechanical excitation and energy conversion efficiency at higher airflow velocities. Among the configurations examined, the 1:1 ratio consistently exhibits the highest output voltage and the fastest response, particularly at wind speeds of 7 and 8 m/s, suggesting an optimal mechanical–electrical coupling. The 1:2 configuration shows comparable performance at lower wind speeds, while the 1:3 configuration produces substantially lower voltage output throughout the test duration, reflecting reduced energy transfer effectiveness. Overall, the findings highlight the importance of mechanical configuration and wind speed in determining the performance of piezoelectric wind energy harvesters. The results provide useful design guidelines for optimizing PEH systems intended for self-powered sensors and other low-power electronic applications operating in low-speed wind environments.